Role of organizational justice in determining work outcomes of national and expatriate academic staff in Malaysia - Hassan, Arif; Hashim, Junaidah (Emerald Group Publishing Limited, 2011)
Purpose – The study aims to analyze the differences between national and expatriate academic staff perception of organizational justice in Malaysian institutions of higher learning. It also explores the role of organizational justice in shaping teaching faculties’ attitude (job satisfaction and commitment) and behavioral intention (turnover intention).